2001
DOI: 10.1093/ejo/23.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of cementum and periodontal ligament after continuous intrusion in humans: a transmission electron microscopy study

Abstract: An ultrastructural study of the cementum and periodontal ligament (PDL) changes after continuous intrusion with two different and controlled forces in humans was carried out. Twelve first upper premolars, at stage 10 of Nolla, orthodontically indicated for extraction from six patients (mean age 15.3) were used. They were divided into three experimental groups, distributed intra-individually as follows: control (not moved), continuously intruded for 4 weeks with 50 or 100 cN force, utilizing a precise biomechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
1
41

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 33 publications
8
54
1
41
Order By: Relevance
“…The hydrostatic pressure in the PDL obviously depends on the magnitude of the force being applied. This contradicts the findings of Owman-Moll et al 20,21 and Maltha et al 22 but is in agreement with the findings of Faltin et al, 3,6 Casa et al, 4 and Chan and Darendeliler, 5 who observed that the extent of root resorption depended on the magnitude of the applied force system.…”
Section: Discussionsupporting
confidence: 47%
“…The hydrostatic pressure in the PDL obviously depends on the magnitude of the force being applied. This contradicts the findings of Owman-Moll et al 20,21 and Maltha et al 22 but is in agreement with the findings of Faltin et al, 3,6 Casa et al, 4 and Chan and Darendeliler, 5 who observed that the extent of root resorption depended on the magnitude of the applied force system.…”
Section: Discussionsupporting
confidence: 47%
“…[10][11][12] Hence, a precise and unequivocal diagnostic method of imaging is needed to both prevent and monitor resorption, which is possible only by three-dimensional volumetric evaluation. Currently, cone-beam computed tomography (CBCT), as employed in rapid maxillary expansion and molar intrusion, is the leading tool for in vivo dental imaging in the field of root resorption research.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between root resorption and orthodontic force magnitude is very important to consider and allows orthodontists to manage treatment risk; although several studies have investigated this relationship, [9][10][11][12][13][14][15] no clear consensus has been reached because of study differences, such as methods and samples. We propose that it is necessary to study the relationship between root resorption and orthodontic force using a new method.…”
Section: Introductionmentioning
confidence: 99%